OPTIMASI MESIN PENCARI BAGI SANTRI MAJELIS TA’LIM FAIZUL HAQ CISAUK - Maryanah Safitri; Sita Anggraeni; Tyas Setiyorini; Ibnu Rusdi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2022)
The Faizul Haq Ta'lim Council is a non-formal institution that can make a considerable contribution to the development and progress of the State both before and after independence, as a potential means to convey Islamic da'wah and foster society. The students who study there acquire religious knowledge from the ustadz and ustadzah who teach at the Faizul Haq Ta'lim assembly based on the qura'an and sunnah. To further enrich the treasures and reference sources of religious knowledge, students also get it through internet media, namely with the help of search engines, but there are still many students who have not been able to use it optimally so that the search takes a long time. Therefore, we hold community service activities in the form of webinars to provide information and knowledge related to optimizing the use of search engines to assist students in finding the references they need and provide tips for faster and more effective searches. After holding community service in the form of counseling on search engine optimization for the students of the Faizul Haq Cisauk Ta'lim Council, the students can now use search engines like Google properly and correctly. They feel the difference from the previous one, it takes a long time and it is difficult to find the right reference and according to what they need. Now they can search for the references they need more effectively and efficiently.